Mechanisms of menstrual bleeding and abnormal bleeding. - García Giesmann, J. (2015)
The exact mechanism by which the menstrual bleeding occurs is not completely understood so perfect, though no doubt point out as the main factor of it to the decisive influence of hormonal changes in blood concentration of the vascular system of the endometrium.